The Effect of Mathematics Teachers’ Pedagogical Competence on Students’ Learning Outcomes in Mathematics for Grade XI at Muhammadiyah 3 Senior High School, Sidoarjo - Mohammad Khoirrudin Aamsy; Mohamad Syahri; Dyah Worowirastri Ekowati (Journal of General Education and Humanities, 2026)
Teachers’ pedagogical competence is considered one of the key factors influencing the effectiveness of the learning process and students’ academic achievement. However, differences in pedagogical competence among mathematics teachers, particularly in adapting instructional strategies and technology integration, may contribute to variations in student learning outcomes. Therefore, this study aimed to analyze the effect of mathematics teachers’ pedagogical competence on the learning outcomes of Grade XI students at Muhammadiyah 3 Senior High School, Sidoarjo. This study employed a quantitative approach using an ex post facto research design. The population consisted of teachers and students of Muhammadiyah 3 Senior High School Sidoarjo, in the 2025/2026 academic year. The sample comprised two mathematics teachers and 34 Grade XI students selected through purposive sampling. Data were collected using questionnaires, documentation, observations, and interviews. Data analysis included descriptive statistics, normality and homogeneity tests, Pearson correlation analysis, simple linear regression, F-test, and t-test. The findings revealed that teachers’ pedagogical competence was generally categorized as good, particularly in explaining learning materials, understanding students’ learning needs, selecting appropriate teaching methods, and providing feedback. Students’ mathematics learning outcomes achieved an average score of 79.47, indicating a fairly good level of achievement. Pearson correlation analysis demonstrated a very strong positive relationship between pedagogical competence and learning outcomes (r = 0.987, p < 0.05). Furthermore, the results of the regression analysis, F-test, and t-test confirmed that teachers’ pedagogical competence had a significant positive effect on students’ mathematics learning outcomes.